2023
DOI: 10.1002/cssc.202300465
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Electrocatalysis: Electrolyte Engineering Strategies to Boost Faradaic Efficiency

Loknath Thapa,
C. Retna Raj

Abstract: The electrochemical activation of dinitrogen at ambient temperature and pressure for the synthesis of ammonia has drawn increasing attention. The faradaic efficiency (FE) as well as ammonia yield in the electrochemical synthesis is far from reaching the requirement of industrial‐scale production. In aqueous electrolytes, the competing electron‐consuming hydrogen evolution reaction (HER) and poor solubility of nitrogen are the two major bottlenecks. As the electrochemical reduction of nitrogen involves proton‐c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 159 publications
0
3
0
Order By: Relevance
“…Above results show that N 2 molecule can be activated on both pristine and Co-supported α-MoC(001) surfaces, and there are two typical pathways, the dissociative and associative mecha-nisms for the thermal conversion of activated N 2 into NH 3 . 10 For the dissociative mechanism, the N � N bond of N 2 molecule firstly undergoes a cleavage and leaves two adsorbed N atoms on the surface of catalyst. While in the associative pathway, the N � N bond does not broken until N 2 * is hydrogenated to NNH* species.…”
Section: Competition Between Dissociative and Associative Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…Above results show that N 2 molecule can be activated on both pristine and Co-supported α-MoC(001) surfaces, and there are two typical pathways, the dissociative and associative mecha-nisms for the thermal conversion of activated N 2 into NH 3 . 10 For the dissociative mechanism, the N � N bond of N 2 molecule firstly undergoes a cleavage and leaves two adsorbed N atoms on the surface of catalyst. While in the associative pathway, the N � N bond does not broken until N 2 * is hydrogenated to NNH* species.…”
Section: Competition Between Dissociative and Associative Mechanismsmentioning
confidence: 99%
“…[6][7][8] Considering the energy and environmental costs, it is highly desirable to find an efficient catalyst as an alternative to the traditional ammonia synthesis process and develop environmentally friendly ammonia synthesis. [9,10] For the nitrogen reduction reaction (NRR), it has been demonstrated that the electron-feeding capacity of the catalysts plays an important role in the redox mechanism of N 2 activation. [11,12] It is well known that ammonia synthesis over Fe and Ru metal surfaces is regarded as classical examples for NRR, in which N 2 activation is shown to be a direct N�N cleavage process.…”
Section: Introductionmentioning
confidence: 99%
“…Electrochemical nitrogen reduction reacts nitrogen gas with protons and electrons generated by splitting water in the electrochemical cell, and the electricity could come from renewable sources, thereby allowing for low temperature and ambient operation. However, these methods generally suffer from a large overpotential [ 13 ], low faradaic efficiencies [ 14 ], and poor selectivity [ 15 ] for ammonia production, so many efforts are focused on designing robust electrocatalysts to improve the faradaic efficiency of the NRR [ 16 , 17 , 18 ]. One area that has received relatively little attention has been the development of tailored membranes for NRR cells.…”
Section: Introductionmentioning
confidence: 99%